DEVELOPMENT OF THE LACTIC ACID PERMEABILIZER v-qPCR TECHNIQUE FOR Salmonella spp. DETECTION AND QUANTIFICATION - Quthama AL-ZAIDI; Adelina Georgiana MATACHE; Laura-Dorina DINU; Eleonora CALZONI; Florentina MATEI (AgroLife Scientific Journal, 2024)
In the food industry, one of the biggest challenges is microbial contamination. Viability real-time PCR (v-qPCR) technology has made the detection and quantification of pathogens easier, and some issues remain with the accuracy of the results, especially in samples containing viable and non-viable cells. V-qPCR with propidium monoazide (PMA) and pre-treatment with permeability agents is one promising method to circumvent this issue. Therefore, the aim of the study was to improve the Salmonella spp. detection using a method with lactic acid (LA 5-10 mM) pre-treatment that permeabilized Gram-negative outer membrane. The signal reduction (dCt = 13.97) after 10 mM LA pre-treatment was similar with the reduction in Ct signal (dCt = 13.62) when only PMA treatment was applied to a suspension of non- viable cells. In the case of viable cells, the LA pre-treatment improved the v-qPCR detection. These preliminary studies provide useful information on the use of lactic acid, which has proven to be an effective, cheap and low-toxic permeabilizing agent.
Keywords: lactic acid; PMA; v-qPCR; pathogen detection; food safety application.